Primary School Pupils' Patierns Of Understanding Relating To Germination Of Seeds - Abdullah, Nabilah (2006)
Locally, there is a dearth of research on primary school children's understanding of science concepts. Not much is known about the conceptions they hold of science objects or phenomena and nor do the factors that influence their understanding of concepts. Using a combination of the grounded theory and case study approach, this study sought to examine the patterns of understanding relating to germination of seeds of sixty-two Year Four pupils from two primary schools within the Klang Valley. Each pupil was asked to draw his or her context map, interviewed and sat for a paper-andpencil test twice; once before and another after classroom instruction. The patterns of understanding of seed germination were formed based on their notion of seeds, seed formation, germination process and germination requirements. The findings of the study highlighted several important points on which an evolutionary model of understanding of science concept and a comprehensive a framework for science learning and understanding were generated. First, pupils brought into their classrooms a myriad of non-scientific ideas relating to the understudied concepts, largely influenced by the socio-cultural factors within which they were brought up. These included their home environment, the society, media, religion, belief system, language and metaphors used. Internal factors in the form of previous knowledge and conceptual schema of seeds were also found to have influenced their understanding of germination. However, there were also pupils who were not exposed to seeds and germination during their early years of socialization, resulting in their knowing nothing or very little about those concepts.